APPLICATION INFORMATION ENVIRONMENTALLY FRIENDLY PESTICIDES MAKING USING MICROSOFT VISUAL BASIC 6.0 - Heru Junianto; Irfan. Skom. MMSi Irfan. Skom. MMSi (Jurnal Sistem Informasi, 2003)
So far, people are already accustomed to using synthetic pesticides to eradicate allpests on plants. However unwittingly, the synthesis of high-risk pesticides because itcan poison himself. Therefore, now many people are looking for ways to makeenvironmentally-friendly pesticide and does not pollute the surrounding environment.This application was created to provide information on alternative ways of makingenvironmentally friendly pesticides by using ingredients that come from nature too,by using computerized media so that necessary information can be found quickly.Further, the application is made by Visual Basic 6.0 programming language with theintention that the resulting appearance of this application is the user interface, in otherwords easily used by different types among the users.